Odpowiedzi

Najlepsza Odpowiedź!
A) 3x(x-7) = 3x² - 21 x
b)a²(a+2b-1) = a³ + 2a²b - a²
c)-3xy(x+y-3) = -3x²y - 3xy² + 9xy
d)5x²(x³+3x-1) = 5x(do piątej) + 15x³ - 5x²
e)-2√2(x³+√2x-2) = -2√2x³ - 4x + 4√2
108 4 108
2009-11-02T21:34:16+01:00
A) 3x(x-7)=3x²+(-21x)
b)a²(a+2b-1)= a³+2a²b+(-a²)
c)-3xy(x+y-3)= -3x²y+(-3xy²)+9xy
d)5x²(x³+3x-1)= 5x⁵+15x³+(-5x²)
e)-2√2(x³+√2x-2) = -2√2x³ +(-4x)+4√2

Pozdrawiam! :)
68 3 68
A) 3x(x-7) = 3x²-21x

b)a²(a+2b-1) = a³+2a²b-a²

c)-3xy(x+y-3) = -3x²y-3xy²+9xy

d)5x²(x³+3x-1) = 5x⁵+15x³-5x²

e)-2√2(x³+√2x-2) = -2√2x³-4x+4√2
231 4 231